Development of a Web-Based Dashboard System for Monitoring Study Programme Accreditation Instruments - Gunawan, Agus; Gunadi, I Gede Aris; Dewi, Luh Joni Erawati (Sinkron : jurnal dan penelitian teknik informatika, 2023)
Accreditation is a form of assessment or evaluation of the quality of education, both at the level of study programme and higher education institutions, conducted by independent organizations or bodies external to the universities. BAN-PT is one such external agency responsible for accrediting higher education institutions in Indonesia. However, many universities encounter challenges during the accreditation process, such as the absence of a monitoring system and data integration in the preparation of some documents, which are essential for accreditation. To address this issue, researchers have recognized the need to design and build a system that can aid in the preparation and monitoring of accreditation forms. The system was developed using the Extreme Programming model, which adopts the agile concept as the core of application development. The Extreme Programming model consists of four key activities, namely system planning, system design, code writing, and system testing. Based on the black box testing results, the developed system was found to operate as intended. Based on the benchmark results for each aspect of the UEQ, Attractiveness has a value of 1.69 with the good category, Perspicuity has a value of 1.57 with the above average category, Efficiency has a value of 2.11 with the excellent category, Dependability has a value of 1.68 with the good category, Stimulation has a value of 1.29 with the above average category, and Novelty has a value of 0.86 with the above average category.